Women's Human Rights: The Importance of Human Rights for Women in Indonesia - Fhirnanda, Ditha Yulia; Guilin, Xie; Jiao, Deng (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Currently, the law is still considered discriminatory and unfair. The law should be fair, especially to women. Purpose. The goal is for men and women to have equal rights to participate in social and state activities. Method. This article is made using a quantitative method that conducts research to several people, especially women, so that the author knows whether people know about human rights for women, gender equality, and violence experienced by women and law enforcement against women's human rights. Results. In life, the achievement of equality of the dignity of women has not shown rapid progress. Women are also victims of violence from various parties, both physical violence and psychological violence. Women must also have laws that can protect them. There are many factors that influence the law enforcement process. Conclusion. Therefore, Women's Human Rights is a set of rights inherent in women and the right of women to be treated properly without violence from any party.